اعتراضات ابن مالك على النحاة في كتابه شرح التسهيل " باب كان وأخواتها (Faculty of Education Scientific Journal, 2024)
Tasheel  ALfawaed " book is one of valuable book, and have great benefits we can say this book overwhelmed most grammatical and linguistic compositors as a result of it's contents which has details, explanations and replies to a previous research and contemporaries.What is affected by linguistic research also shortens many unclear methods, and saves time for conducting research, especially since many grammarians and linguists do not have works, or perhaps they were lost, or did not reach us.In " ALtasheel Book" , we found appenions of grammarians in each issue , Ibn- Malek tried analysis explaining , giving reasons and mention most of correct and closest opinions All of these opinions  of Ibn- Maleks push the researcher to write them with it's replies ,and focus on only ( Bab Kaana wa Akhwatiha ) to save time , efforts and for do not exceed requested papers.the researcher spot light on these replies to know the style of Ibn- Malek in analyzing evidences, also replies of previous grammarians with it's scientific and moral values that give the researcher Objectivity and respect the different opinions and the researcher recommended to use style of frest grammarians in replying and arguing by scientific way, even if they are opposite to their opinions